2018
DOI: 10.1177/0300060518786915
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic bacterial profile and drug resistance analysis of community-acquired pneumonia in older outpatients with fever

Abstract: ObjectivesTo study the pathogenic bacterial profile and drug resistance in older patients with community-acquired pneumonia (CAP) in outpatients with fever, and provide evidence to diagnose and treat CAP timely and accurately.MethodsWe studied older (>60 years) patients with CAP in Beijing Shijitan Hospital from 2016 to 2017. Pathogenic bacteria from sputum of patients were isolated and identified and their resistance to antibiotics was tested. Risk factors for multidrug-resistant CAP (MDR-CAP) and clinical ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
3
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 17 publications
4
28
3
2
Order By: Relevance
“…Vaccination either excites or reinforces the immune competence of a host to ward off infection, leading to the activation of macrophages, the production of antibodies, inflammation, and other classic immune reactions. 40 Antibacterial vaccines have been responsible for a drastic reduction in global bacterial diseases. Vaccines made from attenuated whole cells or lysates have been replaced largely by less erectogenic, cell-free vaccines consisting of purified components, including capsular polysaccharides and their conjugates, to protein carriers, as well as inactivated toxins (toxoids) and proteins.…”
Section: Vaccinesmentioning
confidence: 99%
“…Vaccination either excites or reinforces the immune competence of a host to ward off infection, leading to the activation of macrophages, the production of antibodies, inflammation, and other classic immune reactions. 40 Antibacterial vaccines have been responsible for a drastic reduction in global bacterial diseases. Vaccines made from attenuated whole cells or lysates have been replaced largely by less erectogenic, cell-free vaccines consisting of purified components, including capsular polysaccharides and their conjugates, to protein carriers, as well as inactivated toxins (toxoids) and proteins.…”
Section: Vaccinesmentioning
confidence: 99%
“…We summarized the baseline characteristics of the included studies in Table 1 . The 21 eligible articles involved 7,650 patients and 1,360 MDR organisms, of which ten reported the risk factors for MDR GPB and GNB [ 15 , 19 , 26 , 28 , 31 , 33 , 34 , 38 , 39 , 41 ], ten for MDR GNB [ 14 , 16 , 17 , 27 , 29 , 30 , 32 , 35 , 36 , 40 ], and one for MDR GPB [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…The risk of bias of the included articles is listed in Table 2 . The overall risk of bias of 15 articles [ 14 17 , 19 , 27 , 29 31 , 33 , 35 , 36 , 38 , 39 , 41 ] is rated as low, four [ 26 , 34 , 37 , 40 ] as moderate, and two [ 28 , 32 ] as high, indicating that most of the included studies had intermediate or higher quality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the situation of bacterial resistance is severe. Luan's study [16] showed that approximately 30% of P. aeruginosa was resistant when older outpatients were infected with community-acquired pneumonia. In a study by Fink et al [17], monotherapy with 400 mg of ciprofloxacin administered every 8 h resulted in 33% resistance to hospital acquired pseudomonas pneumonia, whilst 500 mg of imipenem given every 6 h or 1000 mg every 8 h resulted in 50% resistance.…”
Section: Discussionmentioning
confidence: 99%